2017
DOI: 10.1089/apc.2017.0125
|View full text |Cite
|
Sign up to set email alerts
|

Financial Barriers and Lapses in Treatment and Care of HIV-Infected Adults in a Southern State in the United States

Abstract: Antiretroviral (ARV) adherence has largely been considered from the perspective of an individual's behavior with less attention given to potential structural causes for lapses in treatment, such as the cost of medications and care. HIV medication expense is typically covered by third party payers. However, private insurance premiums and deductibles may rise, or policies terminated such as with a change in employment. Likewise, a patient's eligibility for publicly funded coverage like state AIDS Drug Assistance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 18 publications
1
19
0
Order By: Relevance
“…(30) Other programs designed to provide affordable HIV treatment exist, however, in a recent study conducted in our source study population, patients reported ongoing financial barriers preventing them from accessing HIV care and ART. (31) In this study, WLWH with longer time on prenatal ART were more likely to receive recommended postpartum HIV care. A number of studies have observed that care received prenatally is associated with postpartum care outcomes.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…(30) Other programs designed to provide affordable HIV treatment exist, however, in a recent study conducted in our source study population, patients reported ongoing financial barriers preventing them from accessing HIV care and ART. (31) In this study, WLWH with longer time on prenatal ART were more likely to receive recommended postpartum HIV care. A number of studies have observed that care received prenatally is associated with postpartum care outcomes.…”
Section: Discussionmentioning
confidence: 72%
“…Among 1416 women participating in the UCHCC, 141 had a live birth between 1996 and 2014 and met study inclusion criteria. The median maternal age at delivery was 28 years (interquartile range [IQR], [24][25][26][27][28][29][30][31][32]. Most women were either non-Hispanic Black (62%) or non-Hispanic White (21%), with 18% of other race/ethnicity including 13% Hispanic ( Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…Mental health and substance use comorbidities are additional well-established barriers to medication adherence [15][16][17]. Despite improved access to government-sponsored health insurance, publicly-insured PWH also face structural barriers to health care such as medication copays (a one dollar copay for each DC Medicaid prescription can be a significant financial obstacle for some), decreased health literacy, difficulty renewing public insurance in a timely manner to prevent medication discontinuation, and lack of transportation to pharmacies for medication retrieval [18,19]. Clinical indicators endorsed by the IOM are a one-sizefits-all approach and do not account for insurance status, which may act as a direct marker of socioeconomic status [20].…”
Section: Discussionmentioning
confidence: 99%
“…Mental health and substance use comorbidities are additional well-established barriers to medication adherence (15)(16)(17). Despite improved access to government-sponsored health insurance, publicly-insured PWH also face structural barriers to health care such as medication copays (a one dollar copay for each DC Medicaid prescription can be a significant financial obstacle for some), decreased health literacy, difficulty renewing public insurance in a timely manner to prevent medication discontinuation, and lack of transportation to pharmacies for medication retrieval (18,19).…”
Section: Discussionmentioning
confidence: 99%